2005
DOI: 10.1002/uog.1934
|View full text |Cite
|
Sign up to set email alerts
|

Fetal echocardiographic evaluation of atrial morphology and the prediction of laterality in cases of heterotaxy syndromes

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 29 publications
1
43
1
1
Order By: Relevance
“…Although, prenatal diagnosis of atrial isomerism based upon the configuration of the atrial appendages has been reported,21 the marked variability in configuration of the atrial appendages makes prenatal diagnosis based on echocardiographic morphology alone difficult. Lung lobation cannot be assessed on ultrasound and the recognition of normal bronchial branching patterns has not to date been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although, prenatal diagnosis of atrial isomerism based upon the configuration of the atrial appendages has been reported,21 the marked variability in configuration of the atrial appendages makes prenatal diagnosis based on echocardiographic morphology alone difficult. Lung lobation cannot be assessed on ultrasound and the recognition of normal bronchial branching patterns has not to date been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The first criticism that can be raised is that experienced fetal cardiologists may be able to define the morphology of atrial appendages using 2D imaging alone. However, there are no studies in the literature describing this and other expert researchers have concluded that this method of diagnosis would be unreliable13. Another criticism may be that the results were good because the volumes obtained were of good quality and that the same results need to be reproducible by other investigators.…”
Section: Discussionmentioning
confidence: 90%
“…In the former condition, the classic features are bilateral morphological left atrial appendages (left atrial isomerism), multiple cardiac anomalies, bilateral morphological left (bilobed) lungs with hypoarterial bronchi, polysplenia, intestinal malrotation and interruption of the inferior vena cava with azygos continuation4–12. Conversely, in right isomerism typical anomalies are bilateral morphological right atrial appendages (right atrial isomerism), multiple cardiac anomalies, bilateral morphological right (trilobed) lungs with epiarterial bronchi, asplenia and a malpositioned inferior vena cava, which may be anterior or juxtaposed to the aorta4–13.…”
Section: Introductionmentioning
confidence: 99%
“…Although prenatal diagnosis of right atrial isomerism based upon the configuration of the atrial appendages has been previously reported in case reports [20] and reconfirmed thereafter [8,10,29], the marked variability in configuration of the atrial appendages makes it difficult to reach the prenatal diagnosis based on morphology alone. In the present series, isomerism of the atrial appendages was detected prenatally in only 6 out of 21 foetuses and was also diagnosed in one of the cases in which the diagnosis of right isomerism was rejected postnatally.…”
Section: Discussionmentioning
confidence: 99%